Islamic Bank: Fatwa Perspective from The National Sharia Council of The Indonesian Ulama Council on Resolving Financing Problems - Maulani, Denia; Artasya, Andini Nabilah; Bimo, Widhi Ariyo; Aliyah, Hikmatul (Moneter: Jurnal Keuangan dan Perbankan, 2023)
Financing in Islamic banks has a level of risk that the possibility of default occurs, so it is necessary to analyze the correct financing by bank staff so as not to cause losses and require handling that is fast, precise and in accordance with sharia provisions. This study aims to determine the efforts to resolve problematic financing, the factors causing problematic financing and the suitability of the Fatwa of the National Sharia Council-Indonesian Ulema Council with existing financing at PT.BPRS Amanah Ummah. Qualitative-descriptive method by collecting data through interviews and documentations. During 2022, the percentage of non-performing financing at PT.BPRS Amanah Ummah Bogor Branch is 0% lower than the maximum percentage limit for non-performing financing determined Bank Indonesia of 5%, the performance of PT.BPRS Amanah Ummah Bogor Branch in 2020 -2022 is categorized as very healthy. Efforts made by PT.BPRS Amanah Ummah in dealing with problematic financing, namely taking an intensive approach to financing customers, providing customer summons, rescheduling and selling joint guarantees. Factors causing problematic financing consist of bank internal factors and bank external factors. Settlement of non-performing financing at PT.BPRS Amanah Ummah with the DSN-MUI Fatwa is in accordance with the review of the DSN-MUI Fatwa No.48/DSN-MUI/II/2005 concerning rescheduling murabahah bills and DSN-MUI Fatwa No.47/DSN-MUI /II/2005 concerning the settlement of murabahah receivables for customers unable to pay.